2013
DOI: 10.1177/1947603513480024
|View full text |Cite
|
Sign up to set email alerts
|

Local Morphological Response of the Distal Femoral Articular–Epiphyseal Cartilage Complex of Young Foals to Surgical Stab Incision and Potential Relevance to Cartilage Injury and Repair in Children

Abstract: Objective: Describe the local morphological response of the articular–epiphyseal cartilage complex to surgical stab incision in the distal femur of foals, with emphasis on the relationship between growth cartilage injury, enchondral ossification, and repair. Design: Nine foals were induced into general anesthesia at the age of 13 to 15 days. Four full-thickness stab incision defects were created in the cartilage on the lateral aspect of the lateral trochlear ridge of the left distal femur. Follow-up examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The number of foals and time to follow-up examination was based on previous studies in piglets 20,29 . Local morphological changes at the site of transecting incisions are described separately 30 .…”
Section: Follow-up Examinationmentioning
confidence: 99%
“…The number of foals and time to follow-up examination was based on previous studies in piglets 20,29 . Local morphological changes at the site of transecting incisions are described separately 30 .…”
Section: Follow-up Examinationmentioning
confidence: 99%
“…8). 85,88,130 Chondrocyte proliferation was observed in response to both surgical incisions 80 and ischemic chondronecrosis 78 and is considered a response that is nonspecific with respect to the inciting insult. Vascular proliferation has, however, only been observed adjacent to lesions that include necrosis of vessels and may therefore be specific to ischemic insult.…”
Section: Diagnostic Imaging Studiesmentioning
confidence: 99%
“…Vascular proliferation has, however, only been observed adjacent to lesions that include necrosis of vessels and may therefore be specific to ischemic insult. 78,80 Vascular proliferation was first noted in histological sections cut from decalcified tissue. 85,130 The micro-CT was carried out prior to decalcification of the tissue, and in scans, proliferating vessels were surrounded by focal mineral opacity and compatible with formation of separate centers of endochondral ossification (Fig.…”
Section: Diagnostic Imaging Studiesmentioning
confidence: 99%
“…There was a linear relationship between the number of cells in the largest cluster and the ratio of average SHG intensity in a lesion to the average SHG intensity in the adjacent deep resting zone. Because cluster size previously was shown in experimental studies to increase with time after appearance of lesion, the same may also be concluded about changes in the collagen matrix. The lesions showing fewer responses were located most superficially in the growth cartilage, whereas lesions located at the ossification front had more changes.…”
Section: Discussionmentioning
confidence: 75%
“…Proliferation is seen as increased numbers of cells within a single lacuna, which is then referred to as a cluster, proliferative nest, or chondrone . Clusters have been observed in response to ischemic necrosis, experimental incisions . and in conjunction with osteoarthritis and are therefore regarded as a non‐specific response to insult.…”
mentioning
confidence: 99%